Tegumentary manifestations of Noonan and Noonan-related syndromes (Clinics, 2013)
OBJECTIVES: Noonan and Noonan-related syndromes are common autosomal dominant disorders with neuro-cardio-facial-cutaneous and developmental involvement. The objective of this article is to describe the most relevant tegumentary findings in a cohort of 41 patients with Noonan or Noonan-related syndromes and to detail certain aspects of the molecular mechanisms underlying ectodermal involvement. METHODS: A standard questionnaire was administered. A focused physical examination and a systematic review of clinical records was performed on all patients to verify the presence of tegumentary alterations. The molecular analysis of this cohort included sequencing of the following genes in all patients: PTPN1, SOS1, RAF1, KRAS, SHOC2 and BRAF. RESULTS: The most frequent tegumentary alterations were xeroderma (46%), photosensitivity (29%), excessive hair loss (24%), recurrent oral ulcers (22%), curly hair (20%), nevi (17%), markedly increased palmar and plantar creases (12%), follicular hyperkeratosis (12%), palmoplantar hyperkeratosis (10%), café-au-lait spots (10%) and sparse eyebrows (7%). Patients with mutations in PTPN11 had lower frequencies of palmar and plantar creases and palmar/plantar hyperkeratosis compared with the other patients. CONCLUSIONS: We observed that patients with mutations in genes directly involved in cell proliferation kinase cascades (SOS1, BRAF, KRAS and RAF1) had a higher frequency of hyperkeratotic lesions compared with patients with mutations in genes that have a more complex interaction with and modulation of cell proliferation kinase cascades (PTPN11).